Ethiopia : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Requests for Augmentation of Access and for Waiver of Performance Criterion, and Second Annual Program. (IMF Staff Country Reports; Country Report, 2002)
This paper assesses Ethiopia's Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), and Requests for Augmentation of Access and for Waiver of Performance Criterion, and Second Annual Program. Performance under the first annual PRGF-supported program was satisfactory in the context of Ethiopia's steady progress toward peace with Eritrea. All quantitative and structural performance criteria through October 2001 were observed, with the exception of the adjusted performance criterion on the net domestic assets of the National Bank of Ethiopia, for which the authorities request a waiver.